Pan-cancer landscape analysis of NOP58 and its oncogenic driving role in lung adenocarcinoma - Shushu Qian; Huafeng Liu; Min Zhang; Li Zhang; Yunlan Dai; Xiangming Ye; Wanshun Wen; Ruidong Cheng (Scientific Reports)
Abstract Despite improvements in treatment in recent years, patients with lung adenocarcinoma (LUAD) still face poor prognoses. In this study, we elucidated the potential role of NOP58 ribonucleoprotein in pan-cancer and validated its oncogenic significance in LUAD using bioinformatics and in vitro and in vivo functional assays. NOP58 was found to be overexpressed in various types of tumors. It had great precision for predicting 20 distinct cancer types using receiver operating characteristic curve (ROC) as well as significant connections with the prognoses in particular cancers. In LUAD, NOP58 expression was correlated substantially with the TNM stage, pathologic stage, smoking status, and effectiveness endpoints, when we analyzed its association with clinical characteristics in LUAD. Elevated NOP58 expression was shown as connected with Th2 cell infiltration while also negatively linked with infiltrating other immune cells, such as CD8 T, cytotoxic, and Th1. By inhibiting NOP58 within the LUAD cells, we found a decrease in cells’ capability to proliferate, migrate, and invade. Knockdown of NOP58 inhibited tumor growth in mouse xenograft models. Furthermore, the tissue microarray study indicated that there was a greater expression of NOP58 in the tumor tissues compared to adjacent normal tissues in LUAD. Our findings revealed that NOP58 could be an outstanding bio-index for pan-cancer diagnosis and prognosis and an independent prognostic risk factor in LUAD.